Erdheim-Chester disease: MR of intraaxial and extraaxial brain stem lesions. - Martinez, R (American Journal of Neuroradiology, 1995)
A case of Erdheim-Chester disease demonstrates cerebral hemispheric involvement, as well as and intraaxial and extraaxial brain stem involvement in a patient with symptoms of paraparesis, urinary incontinence, visual loss, ataxia, vertigo, proptosis, and nystagmus. Persistent gadopentetate dimeglumine enhancement was noted in the extraaxial cervicomedullary brain stem lesion 23 days after injection. However, the supratentorial lesions fail to show similar persistent enhancement. This case also demonstrates MR features characteristic of retrobulbar infiltration.